2020
DOI: 10.2147/oas.s268009
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knowledge and Perception of Ethiopian Surgical Patients to Informed Consent Practice for Surgical Procedures</p>

Abstract: Background: Surgical informed consent (SIC) is an established ethical and legal requirement for surgical treatment. Patient understanding of the process is essential for efficient surgical care. This study aimed to assess the knowledge and perception of operated patients towards surgical informed consent. Methods: An institution-based cross-sectional study of all adult surgical patients who signed informed consent and underwent surgery at St. Paul's Hospital Millennium Medical College (SPHHMC) from February 1s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…e points were totaled, and a score of five was assigned. A patient's knowledge was assessed to be poor if he or she scored 0 to 1, unsatisfactory if he or she scored 2 to 3, satisfactory if he or she scored 4 to 5, and good if he or she scored 4 to 5 [22]. In this study, the overall knowledge was recategorized as follows: a score of 4 to 5 was judged as good knowledge; a score below 4 was categorized as poor knowledge.…”
Section: Data Collection Tools Andmentioning
confidence: 99%
“…e points were totaled, and a score of five was assigned. A patient's knowledge was assessed to be poor if he or she scored 0 to 1, unsatisfactory if he or she scored 2 to 3, satisfactory if he or she scored 4 to 5, and good if he or she scored 4 to 5 [22]. In this study, the overall knowledge was recategorized as follows: a score of 4 to 5 was judged as good knowledge; a score below 4 was categorized as poor knowledge.…”
Section: Data Collection Tools Andmentioning
confidence: 99%
“…Knowledge and perception of the client towards informed consent in the primary study were assessed in the composite variable. Knowledge of informed consent is measured by the know reason why they had surgery, the option of alternative treatment, type of surgery, anesthesia-related risks, postoperative care, the complication of surgery, the legal requirement of informed consent, the right to change their mind after sign, and who protects [ 13 , 14 ]. Different literature indicated that patient knowledge of informed consent is low.…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, the magnitude of good knowledge of informed consent among surgical patients is low ranging from 10.5% [ 13 ] to 46.9% [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, only 10.5% of the respondents had a good level of knowledge, and it was significant in those with some level of formal education and in patients who live in an urban area than their respective groups. 10…”
Section: Introductionmentioning
confidence: 99%